First demonstration of "Leaky Integrate and Fire" artificial neuron behavior on (V0.95Cr0.05)2O3 thin film. (15th May 2018) - Adda, Coline; Cario, Laurent; Tranchant, Julien; Janod, Etienne; Besland, Marie-Paule; Rozenberg, Marcelo; Stoliar, Pablo; Corraze, Benoit
Abstract: Abstract : A great challenge in the field of neurocomputing is to mimic the brain behavior by implementing artificial synapses and neurons directly in hardware. This work shows that a Leaky Integrate and Fire (LIF) artificial neuron can be realized with a two-terminal device made of Mott insulator thin films. Polycrystalline thin films of the well-known Mott insulator oxide (V0.95 Cr0.05 )2 O3 were deposited by magnetron sputtering and patterned with micron-scale TiN electrodes. These devices exhibit a volatile resistive switching and a remarkable LIF behavior under a train of pulses suggesting that LIF artificial neurons may be realized from (V0.95 Cr0.05 )2 O3 thin films.